Integrative Transcriptomic and microRNAomic Profiling Reveals Immune Mechanism for the Resilience to Soybean Meal Stress in Fish Gut and Liver - Wu, Nan; Wang, Biao; Cui, Zheng-Wei; Zhang, Xiang-Yang; Cheng, Ying-Yin; Xu, Xuan; Li, Xian-Mei; Wang, Zhao-Xi; Chen, Dan-Dan; Zhang, Yong-An (Frontiers in Physiology, 2018)
In aquafeeds, fish-meal has been commonly replaced with plant protein, which often causes enteritis. Currently, foodborne enteritis has few solutions in regards to prevention or cures. The recovery mechanism from enteritis in herbivorous fish, may further help understand prevention or therapy. However, few reports could be found regarding the recovery or resilience to fish foodborne enteritis. In this study, grass carp was used as an animal model for soybean meal induced enteritis and it was found that the fish could adapt to the soybean meal at a moderate level of substitution. Resilience to soybean meal stress was found in the 40% soybean meal group for juvenile fish at growth performance, morphological and gene expression levels, after a 7-week feeding trial. Furthermore, the intestinal transcriptomic data, including transcriptome and miRNAome, was applied to demonstrate resilience mechanisms. The result of this study revealed that in juvenile grass carp after a 7-week feeding cycle with 40% soybean meal, the intestine recovered via enhancing both an immune tolerance and wound healing, the liver gradually adapted via re-balancing immune responses, such as phagosome and complement cascades. Also, many immune factors in the gut and liver were systemically revealed among stages of on-setting, remising, and recovering (or relief). In addition, miRNA regulation played a key role in switching immune states. Thus, the present data systemically demonstrated that the molecular adaptation mechanism of fish gut-liver immunity is involved in the resilience to soybean meal stress.